2005
DOI: 10.1176/appi.ajp.162.1.178
|View full text |Cite
|
Sign up to set email alerts
|

Is Depression in Old Age Fatal Only When People Feel Lonely?

Abstract: The data suggest that the increased mortality risk attributable to depression in the presence of perceived loneliness may result from motivational depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 15 publications
5
69
1
6
Order By: Relevance
“…Negative interactions, which have not generally been taken into consideration when studying social networks and mental health, may help explain these relationships [6]. In general, the findings of the present study are also consistent with by the model suggested by Cacioppo et al According to these authors, loneliness occurs in clusters, extends up to three degrees of separation in the social network, is disproportionately represented at the periphery of social networks, and spreads through a contagious process [28]. Rosenquist et al also suggested that depression followed a similar process of spreading through the social network, with higher levels of depression in individuals with a smaller number of contacts [29].…”
Section: Discussionsupporting
confidence: 91%
“…Negative interactions, which have not generally been taken into consideration when studying social networks and mental health, may help explain these relationships [6]. In general, the findings of the present study are also consistent with by the model suggested by Cacioppo et al According to these authors, loneliness occurs in clusters, extends up to three degrees of separation in the social network, is disproportionately represented at the periphery of social networks, and spreads through a contagious process [28]. Rosenquist et al also suggested that depression followed a similar process of spreading through the social network, with higher levels of depression in individuals with a smaller number of contacts [29].…”
Section: Discussionsupporting
confidence: 91%
“…The health effects of loneliness have been less well studied than those of social networks, however, loneliness has been associated with a variety of negative health outcomes (O'Luanaigh and Lawlor, 2008), including an increased risk of all cause mortality (Seeman, 2000), and of suicide (Waern et al, 2003). The lonely have an increased risk of depression (Cacioppo et al, 2006) and one study reported that the excess mortality in the elderly depressed was confined to those who were lonely (Stek et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Chronic feelings of loneliness may indicate negative health consequences including high blood pressure, worsened immune and cognitive function, anxiety, depression, suicidal ideation, and subsequently, increased mortality. [4][5][6][7][8][9] Older immigrants are especially vulnerable to loneliness since they may encounter tremendous changes in their social lives while adapting to living in another country. Many older immigrants struggle to maintain their international social connections, and further, linguistic and cultural barriers impede their efforts to establish new social networks and relationships in the host country.…”
Section: Introductionmentioning
confidence: 99%